Orally Bioavailable 6-Chloro-7-methoxy-4(1H)-quinolones Efficacious against Multiple Stages of Plasmodium - Cross, R. Matthew (J Med Chem, 2014)
[Image: see text] The continued proliferation of malaria throughout temperate and tropical regions of the world has promoted a push for more efficacious treatments to combat the disease. Unfortunately, more recent remedies such as artemisinin combination therapies have been rendered less effective due to developing parasite resistance, and new drugs are required that target the parasite in the liver to support the disease elimination efforts. Research was initiated to revisit antimalarials developed in the 1940s and 1960s that were deemed unsuitable for use as therapeutic agents as a result of poor understanding of both physicochemical properties and parasitology. Structure–activity and structure–property relationship studies were conducted to generate a set of compounds with the general 6-chloro-7-methoxy-2-methyl-4(1H)-quinolone scaffold which were substituted at the 3-position with a variety of phenyl moieties possessing various properties. Extensive physicochemical evaluation of the quinolone series was carried out to downselect the most promising 4(1H)-quinolones, 7, 62, 66, and 67, which possessed low-nanomolar EC(50) values against W2 and TM90-C2B as well as improved microsomal stability. Additionally, in vivo Thompson test results using Plasmodium berghei in mice showed that these 4(1H)-quinolones were efficacious for the reduction of parasitemia at >99% after 6 days.